2016
DOI: 10.1159/000447821
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Inhalational Tobramycin-Colistin-Combination in CF-Patients with Chronic P. Aeruginosa Colonization - an Observational Study

Abstract: Background/Aims: In cystic fibrosis (CF), chronic microbial lung infections are difficult to treat and cause morbidity and increased mortality. Methods: In a multicentre, open-label, exploratory, non-interventional study, inhaled tobramycin (300 mg twice daily) and colistin (1 million I.U. twice daily) were sequentially combined with the aim to investigate the effect on 41 CF patients with chronic P. aeruginosa infections for six months (mean age 24 ± 10.8y). Results: Six patients had adverse events that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…This modification is highly relevant in the clinical setting as aminoarabinose modification of lipid A is commonly observed in polymyxin-tolerant P. aeruginosa isolates ( 70 , 71 ). Nebulized colistin is commonly used to reduce P. aeruginosa burdens in the lungs of CF patients ( 72 74 ). Our results suggest that CP released during the inflammatory response in the CF lung may promote P. aeruginosa to tolerate this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This modification is highly relevant in the clinical setting as aminoarabinose modification of lipid A is commonly observed in polymyxin-tolerant P. aeruginosa isolates ( 70 , 71 ). Nebulized colistin is commonly used to reduce P. aeruginosa burdens in the lungs of CF patients ( 72 74 ). Our results suggest that CP released during the inflammatory response in the CF lung may promote P. aeruginosa to tolerate this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While we did not address the mechanism in this study, the observed upregulation of ArnA and ArnB suggests that the increased resistance occurs through the addition of aminoarabinose to lipid A (62, 64) This modification is highly relevant in the clinical setting as aminoarabinose modification of lipid A is commonly observed in polymyxin-resistant P. aeruginosa isolates (72, 73). Nebulized colistin is commonly used to reduce P. aeruginosa burdens in the lungs of CF patients (7476). Our results suggest that CP released during the inflammatory response in the CF lung may promote P. aeruginosa to resist this treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Given that ceramide also plays a very critical role in cystic fibrosis and normalization of ceramide levels by blockers of the acid sphingomyelinase has been shown to prevent infection and inflammation in cystic fibrosis patients [42][43][44], we hypothesize that a therapy that combines normalization of ceramide levels with inhalation of glucosylceramide and/ or sphingosine [17,37] might be the most promising way preventing or treating existing bacterial infection in CF patients in the future. Since other drugs, like antibiotics, can also be applied via an inhalation therapy in CF [45], this way of application offers the benefits of a local administration with minimal adverse systemic effects. It has to be proved if administration of GBA2 inhibitors can also be applied via inhalation and if a combination therapy of ceramide reducing and GlcCer stabilizing/generating strategy is more promising than application of one drug alone.…”
Section: Discussionmentioning
confidence: 99%